Association between aquaporin 3 and transforming growth factor-beta 1 levels in decidual tissue and serum of patients with missed abortion - JinLing Yuan; JianXin Dong; Wanting Li; YingMo Zu; YanJuan Guo; Ying Zhang; Yan Chen (Frontiers in Medicine)
ObjectiveTo investigate the expression of aquaporin 3 (AQP3) and transforming growth factor-β1 (TGF-β1) in the decidual tissue and serum of patients with missed abortion (MA) and explore their clinical significance, evaluating their potential as diagnostic biomarkers for MA.MethodsA total of 40 MA patients (case group) and 40 induced abortion (IA) patients (control group) were included. Immunohistochemistry (IHC), Western blot (WB), and reverse transcription quantitative PCR (RT-qPCR) were used to detect the protein and mRNA expression of AQP3 and TGF-β1 in decidual tissue. Serum levels of AQP3 and TGF-β1 were measured by ELISA. The diagnostic efficacy was assessed using receiver operating characteristic (ROC) curve analysis.ResultsThe protein expression of AQP3 and TGF-β1 in the decidual tissue of the MA group was significantly higher than that of the IA group, with a 2.3-fold and 2.5-fold increase, respectively (p < 0.01), and their mRNA expression was also significantly upregulated (p < 0.01). Serum levels of AQP3 and TGF-β1 increased by 2.3-fold and 3.3-fold, respectively (p < 0.01). ROC analysis demonstrated that serum AQP3 (AUC = 0.887) and TGF-β1 (AUC = 0.949) exhibited high diagnostic accuracy for MA, with the combined detection achieving an AUC of 0.976, sensitivity of 92.5%, and specificity of 97.5%.ConclusionAQP3 and TGF-β1 are significantly overexpressed in the decidual tissue and serum of MA patients and may play a role in the pathogenesis of MA by regulating trophoblast function. The combined detection of these two biomarkers holds promise as potential diagnostic tools for MA, offering new directions for early clinical management.